2016
DOI: 10.1016/j.cmet.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Environment Dictates Dependence on Mitochondrial Complex I for NAD+ and Aspartate Production and Determines Cancer Cell Sensitivity to Metformin

Abstract: Summary Metformin use is associated with reduced cancer mortality, but how metformin impacts cancer outcomes is controversial. While metformin can act cell autonomously to inhibit tumor growth, the doses of metformin that inhibit proliferation in tissue culture are much higher than what has been described in vivo. Here, we show that environment drastically alters sensitivity to metformin and other complex I inhibitors. We find that complex I supports proliferation by regenerating NAD+, and metformin’s anti-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
300
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(337 citation statements)
references
References 55 publications
(75 reference statements)
25
300
1
Order By: Relevance
“…Although the precise mechanism of metformin action remains controversial (Luengo et al, 2014), recent work has shown that the anti-tumorigenic effect of metformin can at least be partially accounted for by direct mitochondrial complex I inhibition in tumors (Gui et al, 2016; Wheaton et al, 2014). Consistent with this notion, other complex I inhibitors have shown efficacy as anti-tumor agents (Appleyard et al, 2012; Schockel et al, 2015) and may show selective toxicity against oncogene-ablation resistant cells (Viale et al, 2014) and cancer stem cells (Sancho et al, 2015).…”
Section: Emerging Metabolic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanism of metformin action remains controversial (Luengo et al, 2014), recent work has shown that the anti-tumorigenic effect of metformin can at least be partially accounted for by direct mitochondrial complex I inhibition in tumors (Gui et al, 2016; Wheaton et al, 2014). Consistent with this notion, other complex I inhibitors have shown efficacy as anti-tumor agents (Appleyard et al, 2012; Schockel et al, 2015) and may show selective toxicity against oncogene-ablation resistant cells (Viale et al, 2014) and cancer stem cells (Sancho et al, 2015).…”
Section: Emerging Metabolic Targetsmentioning
confidence: 99%
“…Additionally, NAD+ serves as a critical redox cofactor required to generate oxidized molecules, such as amino acids and nucleotides necessary for biomass accumulation (Birsoy et al, 2015; Sullivan et al, 2015; Titov et al, 2016). Proliferating cells often require a high NAD+/NADH ratio to support anabolic reactions, and in some contexts the NAD+/NADH ratio directly correlates with proliferation rate (Gui et al, 2016). Higher NAD+/NADH ratios appear important for proliferation while lower ratios favor mitochondrial ATP production.…”
Section: Emerging Metabolic Targetsmentioning
confidence: 99%
“…More recently, it has been recognised that complex I inhibition has additional consequences related to accumulation of NADH relative to NAD + , which of course would also be expected to influence cellular biochemistry. One example of this is the inhibitory effect of biguanides on aspartate synthesis [13].…”
Section: Molecular Targetsmentioning
confidence: 99%
“…In assessing the cellular metabolic capacity with Seahorse XF24, the cells exhibited different maximal respiratory capacity that may explain the findings. Gui et al recently attempted to explain the discrepancy between in vitro and in vivo doses of metformin by providing evidence that breast cancer cell sensitivity was dependent on tumour microenvironments such as low NAD+/NADH ratio secondary to lower serine levels [305]. Therefore, when considering metformin doses and various cell type sensitivities, the microenvironment needs to be considered in addition to the cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The upstream regulators of GTPase Pac1 such as P-Rex1, cAMP, and CXCL12/CXCR4 were also downregulated by metformin. Further, the drug decreased lipogenic proteins such as acetyl-CoA carboxylase, fatty acid synthase and sterol regulatory element binding protein-1c resulting in inhibition of lipogenesis of LNCaP and DU145 [305]. Lipogenesis is a key self-propagating mechanism for PCa cell lines which has been observed to be affected by insulin and metformin [5].…”
Section: Metformin and Pca Cellsmentioning
confidence: 99%